Aqueous zinc ion bacterial cellulose diaphragm, preparation method and application
By using bacterial cellulose septum prepared by bacterial cellulose hydrogel, the problem of the growth and hydrogen analysis of zinc branch crystals in zinc ion batteries in water -based zinc ion batteries, which significantly improves the cycle life and Kuron efficiency of the battery, realized the metal zinc negative electrode polar Protection.
Patent Information
- Application Number
- CN202411488731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
During operation, due to the activity of the zinc negative electrode, the aqueous zinc ion battery will produce side reactions such as zinc dendrites growth, hydrogen evolution and corrosion, which seriously affects the battery's Coulomb efficiency and cycle life.
Using bacterial cellulose hydrogel as raw material, through soaking, drying and re-soaking, an integrated bacterial cellulose separator containing electrolyte is prepared to reduce side reactions such as zinc dendrite growth and hydrogen evolution.
It effectively suppresses the side reactions of aqueous zinc-ion batteries, significantly improves the cycle life and Coulombic efficiency of the battery, and realizes the protection of the metallic zinc negative electrode.
Smart Images

Figure CN119361965A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion bacterial cellulose diaphragm, a preparation method and application thereof. Background Art
[0002] At a time when energy crisis and environmental pollution are serious, new energy is developing rapidly and the demand for electric vehicles is increasing. Developing large-scale energy storage with high energy / power density and high energy conversion efficiency is an effective strategy to ensure the efficient and stable use of new energy electricity.
[0003] Among various electrochemical energy storage devices, aqueous zinc-ion batteries have broad application prospects due to their high safety, abundant raw material reserves, large theoretical capacity, and environmental friendliness. However, during operation, aqueous zinc-ion batteries will produce zinc dendrite growth, hydrogen evolution, corrosion and other side reactions due to the activity of their zinc negative electrode. These side reactions seriously affect the coulombic efficiency and cycle life of aqueous zinc-ion batteries, hindering the large-scale application of zinc-ion batteries.
[0004] As an indispensable part of the battery composition, the diaphragm has the functions of isolating the positive and negative electrodes and transmitting ions in the battery. The quality of the diaphragm directly affects the interface stability of the battery, the battery capacity, and the long-term safe and stable operation of the battery. By designing a diaphragm for an aqueous zinc ion battery, the occurrence of side reactions can be effectively suppressed, and the cycle life and coulomb efficiency of the aqueous zinc ion battery can be improved. Cellulose is the most abundant natural polymer on the earth. It is a linear natural polymer anhydroglucose with the characteristics of high crystallinity, fibrous and insoluble. Bacterial cellulose (BC) is a cellulose produced by bacteria. It is a typical biomass material with the characteristics of 3D mesh structure, high water binding capacity, high tensile strength, etc., and the material is cheap, rich in sources, non-toxic and harmless, and has outstanding advantages in aqueous zinc ion batteries. Based on the above characteristics, the present invention adopts bacterial cellulose hydrogel as a raw material, and through simple processing, a method for preparing an aqueous zinc ion battery diaphragm is invented.
[0005] The patent application document with publication number CN118292277A discloses an aqueous zinc ion battery separator based on electrospinning and a preparation method thereof, wherein the separator obtained by electrospinning is further heated and impregnated, and then a solvent is added for in-situ polymerization, thereby finally obtaining an aqueous zinc ion battery separator. However, since multiple steps of electrospinning, cross-linking heating, and in-situ polymerization are required, the resulting cost is high and the operation is complicated. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an aqueous zinc ion bacterial cellulose diaphragm, a preparation method and application thereof. By directly soaking, drying and then soaking the bacterial cellulose hydrogel, an integrated bacterial cellulose diaphragm containing an electrolyte is obtained by utilizing its simple replacement reaction mechanism. The diaphragm can reduce the side reactions such as zinc dendrite growth and hydrogen evolution of aqueous zinc ion batteries, and can greatly improve the cycle life and coulomb efficiency of aqueous zinc ion batteries.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are mutually entangled to form a fiber network pore characteristic, and the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state.
[0009] The aqueous zinc ion electrolyte is a 2M ZnSO4 / H2O aqueous zinc ion electrolyte.
[0010] The thickness of the aqueous zinc ion bacterial cellulose membrane is 90um to 120um.
[0011] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0012] Step 1: Soaking bacterial cellulose hydrogel in ethanol solution to obtain dehydrated bacterial cellulose; the bacterial cellulose is (C6H 10 O5) n ;
[0013] Step 2: sandwiching the dehydrated bacterial cellulose membrane obtained in step 1 between two filter papers and drying in a vacuum oven to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0014] Step 3: immersing the dehydrated bacterial cellulose membrane with gaps and pores obtained in step 2 into an aqueous zinc ion electrolyte until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated to obtain an aqueous zinc ion bacterial cellulose membrane; the bacterial cellulose membrane comprises (C6H 10 O5) n .
[0015] The step 1 is specifically as follows:
[0016] Step 1: Soak the bacterial cellulose hydrogel in an ethanol solution for 5-8 hours, repeating the process more than once to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: ethanol solution = (1-2): (4-5).
[0017] The ethanol solution in step 1 is an anhydrous ethanol solution.
[0018] In the step 2, the temperature of the vacuum oven is set to 60° C. to 80° C., and the drying time is 2 to 5 hours.
[0019] The step three is specifically as follows:
[0020] The dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 is immersed in 2M ZnSO4 / H2O aqueous zinc ion electrolyte for 24 to 72 hours to obtain an aqueous zinc ion bacterial cellulose membrane.
[0021] The soaking process is repeated more than once until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated.
[0022] A battery comprises a diaphragm, wherein the diaphragm is the aqueous zinc ion bacterial cellulose diaphragm or the aqueous zinc ion bacterial cellulose diaphragm prepared by any of the above methods.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. In the first step of the present invention, the bacterial cellulose hydrogel is immersed in an ethanol solution to perform a simple replacement reaction, so that the bacterial cellulose hydrogel can be applied in the field of aqueous zinc ion batteries, which is simple, efficient and has excellent performance.
[0025] 2. In step three of the present invention, the dehydrated bacterial cellulose membrane with a gap and pore structure obtained in step two is directly treated by immersing it in an aqueous zinc ion electrolyte to obtain an integrated bacterial cellulose membrane directly containing an electrolyte, which can inhibit side reactions such as dendrite growth and hydrogen evolution in aqueous zinc ion batteries. The prepared aqueous zinc ion battery has a longer cycle life and a higher coulombic efficiency, thereby achieving the purpose of protecting the metallic zinc negative electrode.
[0026] In summary, the present invention obtains an integrated bacterial cellulose membrane directly containing an electrolyte by direct replacement treatment of the bacterial cellulose hydrogel and simple immersion. The obtained aqueous zinc ion bacterial cellulose membrane has the characteristics of being easy to prepare and non-toxic and harmless. The prepared aqueous zinc ion battery has a longer cycle life and higher coulombic efficiency, thereby achieving the purpose of protecting the metal zinc negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a cycle time curve diagram of the battery assembled in Example 1. DETAILED DESCRIPTION
[0028] In order to make the present invention easier to understand, the present invention is further described below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the embodiments described below.
[0029] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The structure is such that the macromolecules are entangled with each other to form a fiber network hole feature, and the fiber network hole contains an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state. The fiber network hole structure based on the intrinsic bacterial cellulose allows for better electrolyte infiltration and better interface contact with the zinc metal negative electrode.
[0030] The aqueous zinc ion electrolyte is a 2M ZnSO4 / H2O aqueous zinc ion electrolyte.
[0031] The thickness of the aqueous zinc ion bacterial cellulose membrane is 90um to 120um.
[0032] The prepared bacterial cellulose membrane can not only meet the density requirements of battery membranes, but also retain the gap and pore characteristics of the original microstructure.
[0033] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0034] Step 1: Soak the bacterial cellulose hydrogel in an anhydrous ethanol solution for 5-8 hours, repeating once or more to obtain dehydrated bacterial cellulose; the bacterial cellulose is (C6H 10 O5) n ; According to the mass ratio, bacterial cellulose hydrogel: anhydrous ethanol solution = (1-2): (4-5);
[0035] The bacterial cellulose hydrogel used in the embodiment of the present invention is a commercially available product.
[0036] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven, wherein the temperature of the vacuum oven is set to 60° C. to 80° C. and the drying time is 2 to 5 hours to obtain a dehydrated bacterial cellulose membrane having a gap and pore structure;
[0037] Step 3: immersing the dehydrated bacterial cellulose membrane with gaps and pores obtained in step 2 in a 2MZnSO4 / H2O aqueous zinc ion electrolyte for 24 to 72 hours, and the immersion process is repeated more than once until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, thereby obtaining an aqueous zinc ion bacterial cellulose membrane; the bacterial cellulose membrane comprises (C6H 10 O5)n .
[0038] A battery comprises a diaphragm, wherein the diaphragm is the aqueous zinc ion bacterial cellulose diaphragm or the aqueous zinc ion bacterial cellulose diaphragm prepared by any of the above methods.
[0039] Example 1
[0040] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are mutually entangled to form a fiber network pore feature, the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state; the aqueous zinc ion electrolyte is 2MZnSO4 / H2O aqueous zinc ion electrolyte; the thickness of the aqueous zinc ion bacterial cellulose membrane is 90um.
[0041] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0042] Step 1: Soak the bacterial cellulose hydrogel in an anhydrous ethanol solution for 5 hours, repeat three times to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: anhydrous ethanol solution = 1:5;
[0043] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven. The temperature of the vacuum oven is set to 60° C. and the drying time is 3 hours to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0044] Step 3: Immerse the dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 in 2MZnSO4 / H2O aqueous zinc ion electrolyte for 24 hours, repeat twice, until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, and obtain an aqueous zinc ion bacterial cellulose membrane.
[0045] Example 2
[0046] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are mutually entangled to form a fiber network pore feature, the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state; the aqueous zinc ion electrolyte is 2MZnSO4 / H2O aqueous zinc ion electrolyte; the thickness of the aqueous zinc ion bacterial cellulose membrane is 100um.
[0047] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0048] Step 1: Soak the bacterial cellulose hydrogel in anhydrous ethanol solution for 6 hours, repeat three times to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: anhydrous ethanol solution = 2:5;
[0049] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven. The temperature of the vacuum oven is set to 60° C. and the drying time is 4 hours to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0050] Step 3: Immerse the dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 in 2MZnSO4 / H2O aqueous zinc ion electrolyte for 32 hours, repeat twice, until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, and obtain an aqueous zinc ion bacterial cellulose membrane.
[0051] Example 3
[0052] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are mutually entangled to form a fiber network pore feature, the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state; the aqueous zinc ion electrolyte is 2MZnSO4 / H2O aqueous zinc ion electrolyte; the thickness of the aqueous zinc ion bacterial cellulose membrane is 115um.
[0053] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0054] Step 1: Soak the bacterial cellulose hydrogel in anhydrous ethanol solution for 8 hours, repeat three times to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: anhydrous ethanol solution = 1:4;
[0055] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven. The temperature of the vacuum oven is set to 80° C. and the drying time is 2 h to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0056] Step 3: Immerse the dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 in 2MZnSO4 / H2O aqueous zinc ion electrolyte for 48 hours, repeat three times, until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, and obtain an aqueous zinc ion bacterial cellulose membrane.
[0057] Example 4
[0058] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are mutually entangled to form a fiber network pore feature, the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state; the aqueous zinc ion electrolyte is 2MZnSO4 / H2O aqueous zinc ion electrolyte; the thickness of the aqueous zinc ion bacterial cellulose membrane is 120um.
[0059] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0060] Step 1: Soak the bacterial cellulose hydrogel in anhydrous ethanol solution for 5 hours, repeat three times to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: anhydrous ethanol solution = 2:5;
[0061] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven. The temperature of the vacuum oven is set to 60° C. and the drying time is 5 hours to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0062] Step 3: Immerse the dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 in 2MZnSO4 / H2O aqueous zinc ion electrolyte for 72 hours, repeat three times, until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, and obtain an aqueous zinc ion bacterial cellulose membrane.
[0063] Example 5
[0064] A water-based zinc ion bacterial cellulose membrane, the bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) nThe macromolecules are mutually entangled to form a fiber network pore feature, the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state; the aqueous zinc ion electrolyte is 2MZnSO4 / H2O aqueous zinc ion electrolyte; the thickness of the aqueous zinc ion bacterial cellulose membrane is 110um.
[0065] A method for preparing an aqueous zinc ion bacterial cellulose diaphragm comprises the following steps:
[0066] Step 1: Soak the bacterial cellulose hydrogel in anhydrous ethanol solution for 5 hours, repeat three times to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: anhydrous ethanol solution = 1:4;
[0067] Step 2: sandwich the dehydrated bacterial cellulose obtained in step 1 between two filter papers and dry it in a vacuum oven. The temperature of the vacuum oven is set to 70° C. and the drying time is 4 hours to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure;
[0068] Step 3: Immerse the dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 in 2MZnSO4 / H2O aqueous zinc ion electrolyte for 48 hours, repeat twice, until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated, so that the zinc electrode can be fully in contact with the electrolyte to ensure the stable operation of the battery, and obtain an aqueous zinc ion bacterial cellulose membrane.
[0069] A battery was prepared using the aqueous zinc ion bacterial cellulose membrane prepared in Example 1 in the following manner.
[0070] The metal zinc sheet is the counter electrode, and the prepared bacterial cellulose membrane has been infiltrated with the electrolyte of the aqueous zinc ion battery and can be used directly to assemble it into a zinc symmetric battery. Figure 1 For the corresponding battery at 1mAcm -2 At a current density of 1 mAh cm -2 The cycle time curve below shows that the zinc symmetric battery can be cycled continuously for up to 1400 hours without significant change in peak current compared with the commercial glass fiber separator, which effectively proves that the membrane can significantly improve its cycle life.
[0071] Compared with the existing aqueous zinc ion battery separators, the aqueous zinc ion bacterial cellulose separator prepared by the present invention can inhibit the side reactions such as dendrite growth and hydrogen evolution of the aqueous zinc ion battery, so that the aqueous zinc ion battery has a longer cycle life and a higher coulomb efficiency, thereby achieving the purpose of protecting the metal zinc negative electrode; and the preparation method of the aqueous zinc ion bacterial cellulose separator of the present invention is simple, and the raw materials are non-toxic and harmless and are easy to obtain.
[0072] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. An aqueous zinc ion bacterial cellulose membrane, characterized in that: The bacterial cellulose membrane is composed of bacterial cellulose macromolecules (C6H 10 O5) n The macromolecules are entangled with each other to form a fiber network pore feature, and the fiber network pores contain an aqueous zinc ion electrolyte, and the aqueous zinc ion electrolyte reaches a saturated state.
2. The aqueous zinc ion bacterial cellulose membrane according to claim 1, characterized in that: The aqueous zinc ion electrolyte is a 2M ZnSO4 / H2O aqueous zinc ion electrolyte.
3. The aqueous zinc ion bacterial cellulose membrane according to claim 1, characterized in that: The thickness of the aqueous zinc ion bacterial cellulose membrane is 90um to 120um.
4. A method for preparing an aqueous zinc ion bacterial cellulose membrane, characterized in that: The following steps are involved: Step 1: Soaking bacterial cellulose hydrogel in ethanol solution to obtain dehydrated bacterial cellulose; the bacterial cellulose is (C6H 10 O5) n ; Step 2: sandwiching the dehydrated bacterial cellulose obtained in step 1 between two filter papers and drying in a vacuum oven to obtain a dehydrated bacterial cellulose membrane with a gap and pore structure; Step 3: immersing the dehydrated bacterial cellulose membrane with gaps and pores obtained in step 2 into an aqueous zinc ion electrolyte until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated to obtain an aqueous zinc ion bacterial cellulose membrane; the bacterial cellulose membrane comprises (C6H 10 O5) n .
5. The method for preparing an aqueous zinc ion bacterial cellulose membrane according to claim 4, characterized in that: The step 1 is specifically as follows: Step 1: Soak the bacterial cellulose hydrogel in an ethanol solution for 5-8 hours, repeating the process more than once to obtain dehydrated bacterial cellulose; according to the mass ratio, the bacterial cellulose hydrogel: ethanol solution = (1-2): (4-5).
6. A method for preparing an aqueous zinc ion bacterial cellulose membrane according to claim 4 or 5, characterized in that: The ethanol solution in step 1 is an anhydrous ethanol solution.
7. The method for preparing an aqueous zinc ion bacterial cellulose membrane according to claim 4, characterized in that: In the step 2, the temperature of the vacuum oven is set to 60° C. to 80° C., and the drying time is 2 to 5 hours.
8. The method for preparing an aqueous zinc ion bacterial cellulose membrane according to claim 4, characterized in that: The step three is specifically as follows: The dehydrated bacterial cellulose membrane with gap and pore structure obtained in step 2 is immersed in 2M ZnSO4 / H2O aqueous zinc ion electrolyte for 24 to 72 hours to obtain an aqueous zinc ion bacterial cellulose membrane.
9. The method for preparing an aqueous zinc ion bacterial cellulose membrane according to claim 8, characterized in that: The soaking process is repeated more than once until the aqueous zinc ion electrolyte in the dehydrated bacterial cellulose membrane is saturated.
10. A battery comprising a separator, characterized in that: The membrane is the aqueous zinc ion bacterial cellulose membrane according to any one of claims 1 to 3 or the aqueous zinc ion bacterial cellulose membrane prepared by any one of the methods according to claims 4 to 9.
Citation Information
Patent Citations
Method for preparing three-dimensional network polymer gel electrolyte film based on bacterial cellulose
CN109841899A
Composite diaphragm as well as preparation method and application thereof
CN116111275A
Biomass fiber-based battery diaphragm as well as preparation method and application thereof
CN116706428A
High-temperature-resistant heat-conducting bacterial cellulose-based diaphragm as well as preparation and application thereof
CN117559080A
Diaphragm, metal ion battery, preparation method and application
CN118137068A
Cited By
Diatomite / nanocellulose composite diaphragm as well as preparation method and application thereof
CN122025996A